Granulomatous diseases of the central nervous system: Approach to diagnosis - Sundaram Challa (Wolters Kluwer Medknow Publications, 2022)
Diagnosis of central nervous system (CNS) granulomas is challenging. The etiology may be infectious or non-infectious. The infectious causes are due to mycobacteria, fungi, parasites and rarely bacteria. The non-infectious causes include autoimmune diseases, diseases of uncertain etiology like sarcoidosis, those associated with neoplasms and reparative processes. Histologic evaluation of type of granuloma as necrotizing, non-necrotizing, fibrotic/calcific or foreign-body type, site of CNS involvement (leptomeninges/dura, brain/spinal cord) and identification of etiologic agent on histochemistry/culture/molecular methods resolves the diagnosis in a many a patient. Correlation with clinical and imaging features, risk factors and route of spread, geographical location and travel history are important. However, diagnosis may remain unresolved despite the application of all available techniques, highlighting the need for better diagnostic techniques.